2020
DOI: 10.1101/2020.03.15.992453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asperosaponin VI inhibits LPS-induced inflammatory response by activating PPAR-γ pathway in primary microglia

Abstract: Microglia cells are the main mediators of neuroinflammation.Activation of microglia often aggravates the pathological process of various neurological diseases. Natural chemicals have unique advantages in inhibiting microglia-mediated neuroinflammation and improving neuronal function. Here, we examined the effects of asperosaponin Ⅵ (ASA Ⅵ) on LPS-activated primary microglia. Microglia were isolated from mice and pretreated with different doses of ASA Ⅵ, following lipopolysaccharide (LPS) administration. Activa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Consistent with that study, we found here that the PPAR-γ agonist pioglitazone, like ASD, induced an anti-in ammatory microglial phenotype. Our ndings here may help explain how ASD can attenuate microglia-mediated in ammation in animal models of depression [31,32].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Consistent with that study, we found here that the PPAR-γ agonist pioglitazone, like ASD, induced an anti-in ammatory microglial phenotype. Our ndings here may help explain how ASD can attenuate microglia-mediated in ammation in animal models of depression [31,32].…”
Section: Discussionmentioning
confidence: 71%
“…PPAR-γ regulates the expression of anti-in ammatory cytokines [56], and the PPAR-γ agonists pioglitazone or rosiglitazone can switch activated microglia cells from a pro-in ammatory to antiin ammatory state [57]. Our previous research showed that ASD acts via PPAR-γ to switch activated microglia from a pro-in ammatory to anti-in ammatory phenotype in vitro [32]. In present study, we further demonstrated that ASD acts via PPAR-γ to induce a pro-neurogenic microglial phenotype in dentate gyrus of CMS-exposed mice and mitigate depressive-like mouse behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial angiogenesis disorders and infection exert key functions in RSA, and it has been shown that AS6 can effectively accelerate the angiogenesis of regenerated tissues and promote wound healing, and promote the vascularization of HUVECs [18]. AS6 can also inhibit the morphological expansion of microglia, reduce the expression of pro-inflammatory cytokines such as IL-1B, iNOS, TNF-α, IL-6, IL-1B, and TNF-α in a dose-dependent manner [19].…”
Section: Discussionmentioning
confidence: 99%
“…e angiogenesis disorders of the endometrium and infection play important part in RSA, and existing evidence has shown that AS6 efficiently accelerates the angiogenesis of regenerated tissue and facilitates wound healing in vivo, and improves vascularization of human umbilical vein endothelial cells (HUVECs) in vitro by the upregulation of HIF-1α/VEGF pathway [18]. Moreover, it has been revealed that AS6 also inhibits the morphological expansion of microglia cells, decreases the expression, and releases of proinflammatory cytokines, such as IL-1B, iNOS, IL-6, and TNF-a in a dosedependent manner [19]. However, whether AS6 can treat RSA through these pathways needs further research.…”
Section: Introductionmentioning
confidence: 99%